Water springs of Volyn region, their classification and spatial location - Мыщенко, О.; Фенко, В. (Київський національний університет імені Тараса Шевченка, 2021)
The scientific interest in the study of water sources is related to their recreational, environmental and sacred significance, as well as the prospect of use in the drinking water supply. The object of this study is the natural water springs of the Volyn region. The methodological basis is a combination of geographical and environmental approaches used in the investigation of the interaction of man and nature. The scientific novelty of the research is the application of a scientific approach to the study of water springs in the Volyn region not only as factors in maintaining water balance but also as objects of worship. The study of geological and hydrogeological preconditions for the formation of water springs in the Volyn region shows that the groundwater of the study area belongs to the bicarbonate class, a group of calcium mainly of the first or second type. The existing classifications of water springs are generalized and adapted to the conditions of Volyn region. The classification of water springs is made on the following features: the direction of water flow, the peculiarity of functioning, the nature of use, hydrological conditions, chemical composition and the level of sacredness. According to the results of the study, it was established that within the study area there were 81 functioning springs, 52 of which are consecrated. The spatial location of water springs in the Volyn region has been studied in the structure of physical and geographical areas. It is established that the largest share of them was formed in Verkhnoprypiatskyi (19), Liubomlsko-Kovelskyi (18) and Turiisko-Rozhyshchenskyi (15) physical-geographical districts. Some consecrated water springs of the Volyn region, which are used as objects of worship, are described, in particular in the villages: Telchi, Vorotniv, Hirka Polonka, Hremiache, Sokil. The widespread disappearance of natural water springs in the Volyn region is due to the natural and anthropogenic factors and is associated not only with their pollution, siltation, drying but also with the depletion of groundwater. In order to preserve and reproduce water springs, we advise continuing to work on their arrangement, to intensify the organization of operational and long-term forecasts of environmental change, monitoring of chemical and biological pollution, certification, and creation of protected areas within them.

Науковий інтерес вивчення водних джерел пов’язаний із їхнім рекреаційним, природоохоронним і сакральним значенням, а також перспективою використання в питному водопостачанні. Об’єктом поданого дослідження є природні водні джерела Волинської області. Методологічною основою служить поєднання географічного й екологічного підходів, що використовуються при вивченні взаємодії людини та природи. Наукова новизна дослідження полягає у застосуванні наукового підходу вивчення водних джерела Волинської області не тільки як чинників підтримання водного балансу території, а і як об’єктів культу. Дослідження геологічних і гідрогеологічних передумов формування водних джерел Волинської області засвідчує, що підземні води досліджуваної території належать до гідрокарбонатного класу, групи кальцію переважно першого або другого типу. Узагальнено існуючі класифікації водних джерел і адаптовано до умов Волинської області. Проведено класифікацію водних джерел за такими ознаками: напрямом водного потоку, особливістю функціонування, характером використання, гідрологічними умовами, хімічним складом, рівнем сакральності. Встановлено, що в межах досліджуваної території налічується 81 функціонуюче джерело, з них 52 – освячені. Досліджено просторове розташування водних джерел Волинської області у структурі фізико-географічних районів. Установлено, що найбільша їхня частка сформувалась у Верхньоприп’ятському (19), Любомльсько-Ковельському (18), Турійсько-Рожищенському (15) фізико-географічних районах. Охарактеризовано окремі освячені водні джерела Волинської області, які використовуються як об’єкти культу, зокрема у селах: Тельчі, Воротнів, Гірка Полонка, Грем’яче, Сокіл. Повсюдне зникнення природних водних джерел Волинської області зумовлено природними й антропогенними чинниками та пов’язане не тільки з їхнім забрудненням, замуленням, висиханням, а й виснаженням підземних вод. З метою збереження та відтворення водних джерел доцільно продовжити роботу щодо їхнього облаштування, активізувати організацію оперативних і довгострокових прогнозів зміни екологічного стану, моніторингу хімічного й біологічного забруднення, паспортизації, створення в їхніх межах природоохоронних територій.
Водні джерела Волинської області: класифікація та просторове розташування
Alekin, O. A., 1970. Osnovy gidrohimii. [Fundamentals of hydrochemistry]. Leningrad: Gidrometeoizdat (In Russia). Zuzuk, L. K., Koloshko, Karpiuk, Z. K., 2012. Osusheni zemli Volynskoi oblasti ta yikh okhorona. [Drained lands of Volyn region and their protection]. Lutsk: Lesya Ukrainka Volyn National University (In Ukrainian). Fesiuk, V. O. (Red.), 2016. Suchasnyi ekolohichnyi stan ta perspektyvy ekolohichno bezpechnoho stiikoho rozvytku Volynskoi oblasti. [Current ecological condition and prospects of ecologically safe sustainable development of Volyn region]. Kyiv: Vienna Enterprise LLC (In Ukrainian). Lange, O. K., 1969. Gidrogeologija. [Hydrogeology]. Moscow: High School (In Russia). Marynych, O. M., Parkhomenko, H. O., Petrenko, O. M., Shchyshchenko, P. H., 2003. Udoskonalena skhema fizyko-heohrafichnoho raionuvannia Ukrainy. [Improved scheme of physical and geographical zoning of Ukraine]. Ukrainian Geographical journal, 1, 16–20 (In Ukrainian). Mishchenko, O. V., 2018. Vodni dzherela Volynskoi oblasti v strukturi sakralnoho landshaftu. [The springs of Volyn region in the structure of the sacred landscape]. Bulletin of Taras Shevchenko National University of Kyiv. Series: Geography, 3 (72), 88 93. DOI: 10.17721/1728-2721.2018.72.15 (In Ukranian). Mishchenko, O., 2018. Classification scheme of sacred landscapes. European Journal of Geography, 9 (4), 62–74. Mishchenko, O. V., 2019. Structural organization of sacred landscapes. Journal of Geology, Geography and Geoecology, 28 (3),487–494. DOI: 10.15421/111944(In Ukrainian). Tarasiuk, N., Hanushchak M., 2017. Rezhym atmosfernoho zvolozhennia gruntiv Volyni v umovakh suchasnoho klimatu. [Regime of atmospheric moistening of Volyn soils in the conditions of modern climate]. Bulletin of Lviv University. Geographic Series, 51, 322–330 (In Ukrainian). Shvec, V. M., Lisenkov A. B., Popov, E. V., 2002. Rodniki Moskvy. Moscow: The scientific world (In Russia). Cherkashyna, M. K., 2016. Problemy pravovoho rehuliuvannia vykorystannia vodnykh dzherel v Ukraini [Problems of legal regulation of water resources use in Ukraine]. Theory and practice of jurisprudence, 1, 1– 17 (In Ukrainian). Siwek, J., Pociask-Karteczka, J., 2017. Springs in South-Central Poland: changes and threats. Institute of Geography and Spatial Management. Jagiellonian University, 40 (1), 38–46.
Keywords: водне джерело; підземні води; класифікація; Волинська область; water spring; groundwater; classification; Volyn region